2008
DOI: 10.1111/j.1526-4610.2008.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Divalproex Extended‐Release in Adolescent Migraine Prophylaxis: Results of a Randomized, Double‐Blind, Placebo‐Controlled Study

Abstract: In the current study, divalproex sodium extended-release did not differentiate from placebo in the prophylactic treatment of migraine headaches but was generally well-tolerated in adolescents aged 12 to 17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 36 publications
10
51
1
3
Order By: Relevance
“…This study shows that the reduction of migraine days achieved by effective migraine prophylaxis is a least partly maintained after termination of prophylaxis at 6 months. Prophylactic treatment with oxcarbazepine [12], divalproex sodium in adolescents [13], and estrogen in menstrual migraine [14] were not effective in migraine prophylaxis.…”
Section: Epilepsy: Evidence-based Medicine and Epidemiological Updatementioning
confidence: 90%
“…This study shows that the reduction of migraine days achieved by effective migraine prophylaxis is a least partly maintained after termination of prophylaxis at 6 months. Prophylactic treatment with oxcarbazepine [12], divalproex sodium in adolescents [13], and estrogen in menstrual migraine [14] were not effective in migraine prophylaxis.…”
Section: Epilepsy: Evidence-based Medicine and Epidemiological Updatementioning
confidence: 90%
“…88 A single unpowered randomized controlled trial examined the risk of individual adverse effects and found no significant differences with divalproex versus placebo based on sparse data. 69 Upper respiratory tract infections were more common with larger doses of divalproex. 69 The results differed depending on the statistical model used.…”
Section: Efficacy and Safety Of Antiepileptic Drugsmentioning
confidence: 99%
“…69 Upper respiratory tract infections were more common with larger doses of divalproex. 69 The results differed depending on the statistical model used. Viral infections were more common with larger doses of divalproex in the models that obtained arcsine-transformed risk differences.…”
Section: Efficacy and Safety Of Antiepileptic Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatotoxicity, thrombocytopenia, increased appetite, and tremor may occur, though it tends to be well tolerated. Open-label trials in children have shown some promise; however, one double-blind, placebo-controlled trial failed to demonstrate superiority over placebo [8][9][10]. Gabapentin is often used due to safety and tolerability and may help to treat comorbid pain conditions.…”
Section: Migraine Without Auramentioning
confidence: 99%